2019
DOI: 10.1155/2019/1434538
|View full text |Cite
|
Sign up to set email alerts
|

Bax Targeted by miR-29a Regulates Chondrocyte Apoptosis in Osteoarthritis

Abstract: Osteoarthritis (OA) is a chronic degenerative joint disease, where chondrocyte apoptosis is responsible for cartilage degeneration. Bax is a well-known proapoptotic protein of the Bcl-2 family, involved in a large number of physiological and pathological processes. However, the regulation mechanisms of Bax underlying chondrocyte apoptosis in OA remain unknown. In the present study, we determined the role of Bax in human OA and chondrocyte apoptosis. The results showed that Bax was upregulated in chondrocytes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…MicroRNAs (miRNAs) play roles in a variety of physiological functions and disease processes by mediating cleavage and destabilization of mRNA [7]. Zhixi Duan et al have illustrated that miR-15a-5p motivates the degeneration and proliferation of chondrocytes through PTHrP inhibition [8].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) play roles in a variety of physiological functions and disease processes by mediating cleavage and destabilization of mRNA [7]. Zhixi Duan et al have illustrated that miR-15a-5p motivates the degeneration and proliferation of chondrocytes through PTHrP inhibition [8].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are well known for their capability to inhibit expression of target genes via binding complementarily to 3′‐UTRs of target mRNAs (Cao et al., 2013; Shukla et al., 2011). Previous studies also reported that several miRNAs, including miR‐573, miR‐208b and miR‐29a, inhibit apoptosis via negative regulation of BAX expression (Miao et al., 2019; Wang et al., 2019; Zhou et al., 2018). In our previous studies, the expression levels of many mRNAs were found to be significantly modulated by miRNAs in GiCF cells during CyHV‐2 infection (Fei, Feng, et al., 2020; Lu, Xu, Shen, et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Caspase-3, a member of cysteine proteases family, is responsible for most of the proteolysis during apoptosis [ 21 ]. Bax is a pro-apoptotic protein in the Bcl-2 family, which is upregulated in chondrocytes of patients with OA [ 22 ]. Bcl2 is an anti-apoptosis protein, whose alteration plays a key role in OA development [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%